Electromagnetic launch systems for civil aircraft assisted take-off - Bertola, Luca; Cox, Tom; Wheeler, Patrick; Garvey, Seamus D.; Morvan, Herve (De Gruyter, 2015)
This paper considers the feasibility of different technologies for an electromagnetic launcher to assist civil aircraft take-off. This method is investigated to reduce the power required from the engines during initial acceleration. Assisted launch has the potential of reducing the required runway length, reducing noise near airports and improving overall aircraft efficiency through reducing engine thrust requirements. The research compares two possible linear motor topologies which may be efficaciously used for this application. The comparison is made on results from both analytical and finite element analysis (FEA).